Fashion dalam Pandangan Islam - Mustiah, Mustiah (PT. Media Edukasi Borneo, 2023)
Prophet Muhammad was sent into the world to enhance human morals. Islam is built on three principles, namely Aqidah (Faith), Syariah (Islamic) and Ihsan (Akhlaq) or commonly known as the Islamic trilogy. Islam comes in line with the human mind, encouraged mutual respect, love and indulgence in private parts that resulted in adultery. Islam does not forbid to follow fashion trends provided in accordance with the teachings of Islam, including thick clothes, body shape is not shaped, close all the nakedness that must be covered and clothing is not thin. How wonderful if true Islamic shariah - correctly applied. Moreover, the womenfolk would be more graceful and wise if wearing a dress in accordance with Islamic Shari'ah. To be able to wear fashion that is similar to the Islam of course be the first condition is the science of religion and the example of our parents and supported by the surrounding environment. Abstrak Rasulullah Muhammad SAW diutus kedunia untuk menyempurnakan akhlak manusia. Islam dibangun atas tiga sendi yaitu Aqidah (Iman ), Syariah ( Islam ) dan Ihsan ( Akhlaq) atau yang biasa dikenal dengan trilogy Islam. Islam datang senada dengan pola pikir manusia, dianjurkan saling menghormati, menyayangi dan tidak mengumbar aurat yang berakibat pada zina. Islam tidak melarang untuk mengikuti perkembangan fashion asalkan sesuai dengan ajaran Islam, diantaranya pakaian tebal, bentuk tubuh tidak berbentuk, menutup semua aurat yang wajib ditutupi dan berbeda pakaian wanita dan pria. Alangkah indahnya jika syari’at Islam benar – benar diterapkan. Apalagi yang kaum hawa akan semakin anggun dan bijaksana jika mengenakan busana sesuai dengan syari’at Islam. Untuk bisa mengenakan fashion yang senada dengan Islam tentunya yang menjadi syarat pertama adalah ilmu agama dan teladan orang tua serta didukung oleh lingkungan sekitar. Kata Kunci: fashion, pandangan Islam, syariat Islam, akhlak.